Preoperative Neutrophil-Lymphocyte Ratio Can Predict Outcomes for Patients Undergoing Tetralogy of Fallot Repair - Manuel,Valdano (2021)
Abstract Introduction: Elevated neutrophil-lymphocyte ratio (NLR) has been associated with poorer outcomes in cyanotic patients undergoing single ventricle palliation. Little is known about this biomarker on patients with tetralogy of Fallot (TOF), the most common cyanotic congenital heart disease. Our objective is to study the impact of preoperative NLR on outcomes of TOF patients undergoing total repair. Methods: This retrospective study included 116 consecutive patients between January 2014 and December 2018. Preoperative NLR was measured from the last complete blood count test before the surgery. Using the cutoff value of 0.80, according to the receiver-operating characteristic (ROC) curve, the sample was divided into two groups (NLR < 0.80 and ≥ 0.80). The primary endpoint was hospital length of stay (LOS). Results: ROC curves showed that higher preoperative NLR was associated with longer hospital LOS, with an area under the curve of 0.801±0.040 (95% confidence interval 0.722 - 0.879; P<0.001). High preoperative NLR was also associated with long intensive care unit (ICU) LOS (P=0.035). Preoperative NLR predicted longer hospital LOS with a sensitivity of 63% and a specificity of 81.4%. Conclusion: Higher preoperative NLR was associated with long ICU and hospital LOS in patients undergoing TOF repair.